Eksperimentasi Model Pembelajaran JUCAMA Ditinjau Dari Gaya Belajar Terhadap Prestasi Belajar Mahasiswa Mata Kuliah Berbicara di Prodi PBSI IKIP PGRI Bojonegoro - Darmuki, Agus; Hariyadi, Ahmad (Universitas Muria Kudus, 2019)
Focus this is research to determine which are the achievements of better speaking learning: (1), learning model JUCAMA or Conventional, (2) Visual, auditory, or kinesthetic, (3) On models learning JUCAMA, which are the achievements of better speaking learning, visual, auditory, or kinesthetic.This type of research is quasi-experimental with 2 × 3 factorial design. The population of this research is all students of PBSI IKSI PGRI Bojonegoro Study Program, which consists of nine classes with a total of 288 students. Sampling was done by cluster random sampling, selected three classes, namely the level of I-A, IB, and IC. The sample consisted of 93 students, with details of 31 IA students as an experiment, 31 IB level students as a control, and 31 IC level students as a trial. Data collection instruments using learning style questionnaires, and learning achievement tests that have been validated by the validators. The test instrument was tested in PBSI level I study program after being tested and then analyzed its reliability, distinguishing features and difficulty levels. The prerequisite tests include the normality test using the Lilliefors method and the variance homogeneity test using the Bartlett method. With ? = 0.05, it can be concluded that the sample comes from populations that are normally distributed and have a homogeneous variance.In this study it can be concluded that: (1) students with learning JUCAMA had speaking learning achievement better than the students with conventional learning, (2) achievement of learning speaking students who have a visual learning style is better than the speaking learning achievement of students who have auditory and kinesthetic learning styles. While the speaking achievement students who have learning styles of auditory as well as students who have a kinesthetic learning style, (3) On learning JUCAMA, there is no difference between speaking achievement in each learning style. Keyword: jucama, learning style, learning achievement, speaking